Financial and Digital Literacy as Moderators in Improving MSME Performance through Financial Management and Digital Marketing in Banyumas - Elora Fitri SolihFahmi, Tsabitah; Purwidianti, Wida (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2025)
MSMEs play an important role in the Indonesian economy, including in Banyumas Regency, which has more than 89.000 business units. However, the low level of digitalization is still a significant obstacle to improving MSME performance. This study aims to analyze the effect of financial management and digital marketing on MSME performance and examine the role of financial literacy and digital literacy as moderating variables. The method used is quantitative, with a survey approach involving 100 MSME owners selected through the Slovin formula. Data analysis was carried out using the PLS-SEM technique. The results of the study showed that financial management and digital literacy had a significant effect on MSME performance. In contrast, digital marketing and financial literacy did not show a significant effect. In addition, financial literacy and digital literacy did not function significantly as moderating variables. These findings indicate that the importance of literacy has not been fully balanced by the ability of MSME owners to apply it in practice. Therefore, this study provides a practical contribution in the form of recommendations for more applicable and sustainable literacy training and a theoretical contribution to of further research that considers other factors that can affect MSME performance.